ANNESTHETIC EFFECTS OF CLOVE OIL ON SURVIVILITY OF GRASS CARP, CTENOPHARYNGODON IDELLA CARP SEED - PAWAN KUMAR, (The Bioscan, 2015)
The aim of this experiment was to investigate the possibilities for using of clove oil as anaesthetic effect in Grass carp Ctenopharyngodon idella. Each test concentration was tested with 10 fish / tank of grass carp having average fingerlings length (65 ± 0.30 mm) and 3.68 g body weight of 90 days old and advanced fingerlings (10.8 ± 1.25 cm) and 15.5 g body weight of 150 days. The tests were carried out under controlled conditions tested at concentration of 0.01, 0.02, 0.03, 0.04, 0.05 and 0.06 μl/L. Experiments were conducted in replicates by adopting standard static bioassay method. The safe application factor equation and safe application rate for the clove oil were also worked out separately for different life history stages of C. idella. The 72 hrs LC50 value exposed clove oil worked out to be 0.050 and 0.029 μl/L for fingerlings and advanced fingerlings. The water quality is determined by temperature, pH, CO2, total ammonia, nitrate, and dissolved oxygen in different concentration. Therefore, present study of clove oil for aquaculture purposes have to encourage because this natural anesthetic is becoming more evident as a safe and low cost alternative.